여고생에게 적용한 인유두종 바이러스 관련 교육의 효과 - 최준영(Choi, Jun-Young); 최소영(Choi, So-Young) (Asian oncology nursing, 2013)
Purpose: This study tried to identify the effects of human papilloma virus related education on the knowledge on human papilloma virus and cervical cancer, and human papilloma virus vaccination intention of teen age female high school students. Methods: The subjects of this study were grade 1 high school girls in K city in December in 2012. 30 high school girls in K high school in K city were assigned to the experimental group and 34 high school girls in J high school in K city were assigned to the control group. Data were analyzed using frequency analysis, percentage, average and standard deviation and t-test verification in the SPSS 18.0 WIN program. Results: There was a significant difference between the two groups as the score of the experimental group increased dramatically (t=27.62, p<.001). There was significant difference between the two groups in cervical cancer knowledge score (t=14.54, p<.001). There was significant difference between the two groups in vaccination intention (t=6.66, p<.001). Conclusion: Therefore, we suggest active promotion of human papilloma virus related education for high school girls in schools.